2017
DOI: 10.1186/s40249-017-0335-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of novel and standard diagnostic tools for the detection of Schistosoma mekongi infection in Lao People’s Democratic Republic and Cambodia

Abstract: BackgroundGiven the restricted distribution of Schistosoma mekongi in one province in Lao People’s Democratic Republic (Lao PDR) and two provinces in Cambodia, together with progress of the national control programmes aimed at reducing morbidity and infection prevalence, the elimination of schistosomiasis mekongi seems feasible. However, sensitive diagnostic tools will be required to determine whether elimination has been achieved. We compared several standard and novel diagnostic tools in S. mekongi-endemic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 41 publications
(70 reference statements)
2
44
1
Order By: Relevance
“…These false positive results encountered in POC-CCA are considered usual because CCA has common epitopes with certain human compounds known as (Lewis X) structures [33]. Here, it is worth mentioning that the lower specificity of POC-CCA (19.18%) as detected in our study and confirmed in other several studies as fore-mentioned, will not prevent its application in surveys for the following reasons: First, people are more compliant to offer a urine sample rather than stool or blood [34]. Second, while Schistosoma eggs continue to be released in stool for few weeks after treatment (viable eggs 2-3 weeks and dead eggs 4-6 weeks), CCA is lowered quickly within one week after treatment; hence, it is a therapeutic monitor [31,35].…”
Section: R E T R a C T E Dsupporting
confidence: 56%
“…These false positive results encountered in POC-CCA are considered usual because CCA has common epitopes with certain human compounds known as (Lewis X) structures [33]. Here, it is worth mentioning that the lower specificity of POC-CCA (19.18%) as detected in our study and confirmed in other several studies as fore-mentioned, will not prevent its application in surveys for the following reasons: First, people are more compliant to offer a urine sample rather than stool or blood [34]. Second, while Schistosoma eggs continue to be released in stool for few weeks after treatment (viable eggs 2-3 weeks and dead eggs 4-6 weeks), CCA is lowered quickly within one week after treatment; hence, it is a therapeutic monitor [31,35].…”
Section: R E T R a C T E Dsupporting
confidence: 56%
“…e status of schistosomiasis in areas that have reached low-transmission was reviewed not long ago [6] and recommendations offered regarding tools and strategies for monitoring, criteria to determine interruption of transmission and validation of elimination. However, these recommendations do not (yet) include the implementation of the newly developed ultrasensitive diagnostic tools [7,8] that allow highly accurate determination of the infection status [9][10][11][12][13][14][15]. It is believed that transmission-stop has been achieved in 19 countries, and currently some already await confirmation of successful steep towards elimination.…”
Section: Introductionmentioning
confidence: 99%
“…21 This ultrasensitive method has been successfully applied to 2 ml endemic urine samples from highand low-transmission areas, indicating prevalences much higher than those measured by microscopy. [21][22][23][24] Additionally, the ultrasensitive UCP-LF CAA assay has demonstrated promise for sample pooling strategies that would allow for large-scale testing, enabling precision mapping for targeted interventions while decreasing overall assay cost. 25 In the shift from morbidity control to elimination, detection of low-burden Schistosoma infections at the point of care will become increasingly important.…”
Section: Introductionmentioning
confidence: 99%